Morphological and Histological Study Of The Cerebrum In A Nocturnal Bird Species (Barn Owl)TytoAlba - Abd-Alrahman, Sh. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Morphological and histoarchitecture aspects on the cerebrum of (barn owl) were made to find outthe cerebrum size, design and the description of cerebral region components at the light microscopic level by using Haematoxylin – Eosin and periodic acid schift (PAS) stain methods. The result of the morphological aspects revealed that the cerebrum was large and an obtuse triangle in shape, its surface had a slight furrow. Sagittal sections revealed the location, arrangement and size of pallial and subpallial cerebral divisions. The result of the microscopic examinations indicated that the large and massive hyperpallium (wulst) was thick,hypertrophied wired, and multilaminate structure reflect their wider stereoscopic night vision. The dorsolateral corticoid area (CDL) contained three different cell groups. The well developed dorsal ventricular ridge (DVR) contained mesopalliumnidopallium and arcopallium, contained voluminous nuclear heterogeneous neuron groups and pyramidal cells. The higher density of the large pyramidal cells were found in the nidopallium (nest pallium) that is surrounding the crescent shap lateral ventricle. The striatum had a striated appearance due to its special histoarchitecture. The pallidum was the smallest and the deepest among cerebral subdivision, it had a pale appearance